Cryo-EM structures of Nipah virus polymerases and high-throughput RdRp assay development enable anti-NiV drug discovery - Zhenhang Chen; Jeanne Quirit Dudley; Colin Deniston; Cosmo Z. Buffalo; Debjani Patra; Dongdong Cao; Julia Hunt; Ahmed Rohaim; Debapriya Sengupta; Lan Wen; Tiffany Tsang; Lili Xie; et al. (Nature Communications)
Abstract Transcription and replication of the Nipah virus (NiV) are driven by the large protein (L) together with its essential co-factor phosphoprotein (P). L encodes all the viral enzymatic functions, including RNA-dependent RNA polymerase (RdRp) activity, while the tetrameric P is multi-modular. Here, we investigate the molecular mechanism of the NiV polymerase and build tools for anti-NiV drug discovery. We analyze and compare multiple cryo-EM structures of both full-length and truncated NiV polymerases from the Malaysia and Bangladesh strains. We identify two conserved loops in the polyribonucleotidyltransferase (PRNTase) domain of L and the binding between RdRp-PRNTase and CD domains. To further assess the mechanism of NiV polymerase activity, we establish a highly sensitive radioactive-labeled RNA synthesis assay and identify a back-priming activity in the NiV polymerase as well as a fluorescence and luminescent-based non-radioactive polymerase assay to enable high-throughput screening for L protein inhibitors. The combination of structural analysis and the development of both high-sensitive and high-throughput biochemical assays will enable the identification of new direct-acting antiviral candidates for treating highly pathogenic henipaviruses.